Atomic force microscopy as a tool for asymmetric polymeric membrane characterization - Abdul Wahab Mohammad; Nidal Hilal; Lim, Ying Pei; Indok Nurul Hasyimah Mohd Amin; Rafeqah Raslan (Universiti Kebangsaan Malaysia, 2011)
Atomic force microscopy (AFM) has a wide range of applications and is rapidly growing in research and development. This powerful technique has been used to visualize surfaces both in liquid or gas media. It has been considered as an effective tool to investigate the surface structure for its ability to generate high-resolution 3D images at a subnanometer range without sample pretreatment. In this paper, the use of AFM to characterize the membrane roughness is presented for commercial and self-prepared membranes for specific applications. Surface roughness has been regarded as one of the most important surface properties, and has significant effect in membrane permeability and fouling behaviour. Several scan areas were used to compare surface roughness for different membrane samples. Characterization of the surfaces was achieved by measuring the average roughness (Ra) and root mean square roughness (Rrms) of the membrane. AFM image shows that the membrane surface was composed entirely of peaks and valleys. Surface roughness is substantially greater for commercial available hydrophobic membranes, in contrast to self-prepared membranes. This study also shows that foulants deposited on membrane surface would increase the membrane roughness.